Influence of Autocratic, Democratic and Laissez-Faire Leadership Styles Towards Nurse’s Job Satisfaction in Inpatient Room of RSU Bhakti Rahayu Tabanan - Nina Rismawati Hakim; I Gede Wirajaya (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The leadership of a nursing manager can create a work environment that decreases nurse turnover, further increases nurse retention and increases patient satisfaction. This study aimed at identifying the influence of the autocratic, democratic and laissez-faire leadership style towards nurse’s job satisfaction in inpatients room at the RSU Bhakti Rahayu Tabanan. Research design used cross sectional with quantitative approach. Data was collected through filling questionnaire of 30 nurses in April 2018 in RSU Bhakti Rahayu Tabanan. Data analysis is multiple linear regression and hypothesis testing using the F test and t test. The results showed that autocratic, democratic and laissez-faire leadership style have a linear influence to nurse’s job satisfaction with F test 86,99 and p value 0,000 was smaller than α = 0,05 (p<0,05) and democratic is the most dominant leadership style that influences towards the nurse’s job satisfaction with t test 4,228